Role of Growth Hormone, Glutamine and Enteral Nutrition in Pediatric Short Bowel Syndrome: A Pilot Follow-Up Study - Guo, M.; Li, Y.; Li, J. (European Journal of Pediatric Surgery, 2012)
Objective Aim of the study was to evaluate whether growth hormone (GH), glutamine (Gln), and enteral nutrition (EN) have a positive effect on intestinal adaptation in pediatric patients with short bowel syndrome (SBS).Method 7 pediatric patients with SBS (small bowel remnant length: 60.57 ± 15.18 cm; mean ± SEM) were treated with GH (0.05 mg∕kg∕day), supplemental Gln (0.45 g∕kg∕day), plus EN for 3 weeks. After 3 weeks of treatment, GH was discontinued, and patients were maintained on Gln and EN or additionally received a high-carbohydrate-low-fat diet. Repeat treatment was given at regular intervals. Changes in weight and height increase, intestinal absorptive capacity and blood indices were evaluated.Result All patients completed the treatment. The intestinal absorptive capacity and plasma levels of proteins were significantly improved after treatment. There were no major adverse effects in any patient and no death occurred. Growth velocity was also well maintained on follow-up. 6 patients were weaned off PN and lived on HCLF diet supplement with EN, while the last patient required less volume of PN.Conclusion Multiple treatment approaches with GH, Gln, and EN at an early stage significantly improved intestinal adaptation in pediatric patients with SBS. Furthermore, the positive effect appeared to be sustained even after GH was discontinued.
Keywords: short bowel syndrome; pediatrics; growth hormone; glutamine; enteral nutrition